Opportunities of the Psychological Diagnostics of Innovation Readiness of the Personality And Organization - V V Panteleyeva (Peoples' Friendship University of Russia (RUDN University), 2011)
The necessity of generalization of the theoretical facts for elaborating the methods for the diagnostics of the innovation readiness level is proved in the article. The results of the experimental research of the innovation readiness factors and the description of the scales of the method are presented.